Tindak Pidana Mengedarkan Sediaan Farmasi Tanpa Izin Edar Menurut UU No. 36 Tahun 2009 Tentang Kesehatan (Studi Putusan Nomor: 739/Pid.Sus/2014/PT-Mdn) - Afifah Naurah salsabilla Nasution; Dedi Gopindo Purba; Juwanda Calvari Ginting Munthe; Sonya Airini Batubara (Universitas Medan Area, 2020)
The rise of drug distribution without a marketing authorization in society is very concern us as members of the community. This shows the level of public awareness of the law is still very low so it tends to commit criminal acts including the distribution of pharmaceutical preparations without marketing authorization. This research was conducted to find out how the legal arrangements against criminal acts circulate pharmaceutical preparations without marketing authorization and the efforts made to overcome them. This research uses normative juridical methods by using secondary data through literature studies. The results of the research conducted can be concluded that the crime of distributing pharmaceutical preparations without marketing authorization regulated in Law No. 36 of 2009 concerning Health functions as optimizing criminal law as a means of preventing crime. The application of this Act is expected to ensnare perpetrators of criminal offenses to circulate pharmaceutical preparations without marketing authorization. As well as the efforts that can be made in handling these criminal acts are carried out with penal and non-penal policies.